1978
DOI: 10.1111/j.1365-3091.1978.tb02077.x
|View full text |Cite
|
Sign up to set email alerts
|

Biolithogenesis of Microcodium: elucidation

Abstract: Petrographic studies of Tertiary and Pleistocene caliche from the western Mediterranean show some unusual calcite structures. These structures were designated Microcodium elegans Glück 1912. New data are presented which question earlier interpretations with regard to the origin of this structure. The new discovery of Microcodium in Recent soils extends its stratigraphic range into the Holocene. Retention of fine detail in Recent samples, revealed by light microscopy and SEM, has suggested an origin hitherto un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(60 citation statements)
references
References 25 publications
2
53
1
2
Order By: Relevance
“…The organization of calcifi ed root cells within rhizoliths resembles problematic features knO\vn as Mi crocodium (Fig. 6D) (Klappa, 1978), especially Microcodium (b) of Estebau (1972) or type 3 ofPlaziat (1984) . Experimental studies on recent roots (Jaillard, 1987;Iaillard et aI., 1991) aud examples from the sedimentary record (Alonso-Zarza et aI., 1998b) indi cate that, very probably, this type of Microcodium is fo rmed by the calcifi cation of root structures with or without the infl uence of other microorganisms.…”
Section: Mic Romorphology and Microscopic Fe Atures Of Calcretesmentioning
confidence: 99%
“…The organization of calcifi ed root cells within rhizoliths resembles problematic features knO\vn as Mi crocodium (Fig. 6D) (Klappa, 1978), especially Microcodium (b) of Estebau (1972) or type 3 ofPlaziat (1984) . Experimental studies on recent roots (Jaillard, 1987;Iaillard et aI., 1991) aud examples from the sedimentary record (Alonso-Zarza et aI., 1998b) indi cate that, very probably, this type of Microcodium is fo rmed by the calcifi cation of root structures with or without the infl uence of other microorganisms.…”
Section: Mic Romorphology and Microscopic Fe Atures Of Calcretesmentioning
confidence: 99%
“…3). The radial fibrous structure is common in calcite coatings and is morphologically similar to Microcodium, a biological structure reported from soil carbonates (Klappa 1978;Freytet and Plaziat 1982;Monger et al 1991). The spherical structures bearing radial fabric are 0.1-0.8 mm in diameter and often exist as large aggregates where the fibrous fabric is sometimes obscured by overlap.…”
Section: Calcite and Hematite Overgrowth Relationshipsmentioning
confidence: 89%
“…During pedogenesis, root respiration produces significant levels of CO 2 (and hence of carbonic acid); additionally, microbial decomposition also releases CO 2 that controls the dissolution and precipitation of pedogenic carbonate (Wright and Tucker 1991;Alonso-Zarza 2003;Brasier 2011). All workers studying Microcodium in relation to the environment of its formation agree on its biogenic, subsurface, non-marine nature (e.g., Klappa 1978;Kabanov et al 2008). Two peaks in Microcodium abundance occur at the Moscovian-Early Permian and latest Cretaceous-Paleogene intervals, which are distinct by low pCO 2 in the atmosphere (Berner 2006;Royer 2006;Kabanov et al 2008).…”
Section: Paleoenvironmental and Paleogeographic Significance Of Calcrmentioning
confidence: 99%
“…Based on a large number of reports, the original interpretation of Microcodium as siphonaceous alga or any other phototrophic microorganism has been rejected; however, the process of Microcodium formation still remains unsolved (Klappa 1978;Alonso-Zarza et al 1998;Košir 2004;Kabanov et al 2008). Microcodium was interpreted as a calcification product of a mycorrhizae-cortical root cell association by Klappa (1978). Alonso-Zarza et al (1998) suggested that 'Microcodium b' formed through calcification of root cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation